The spatial landscape of glial pathology and T cell response in Parkinson’s disease substantia nigra - Maxwell Ma; Fahad Paryani; Kelly Jakubiak; Shengnan Xia; Susumu Antoku; Adithya Kannan; Jaeseung Lee; Nacoya Madden; Shailesh Senthil Kumar; Juncheng Li; David Chen; Gunnar Hargus; et al. (Nature Communications)
Abstract Parkinson’s Disease (PD) is an incurable neurodegenerative disease that causes movement disorders. Neurons in PD aggregate α-synuclein and are depleted from the substantia nigra (SN), which is a movement control hub. The presence of α-synuclein-reactive T cells in PD patient blood suggests a role for adaptive immunity in the pathogenesis of PD. However, the characteristics of this response within the brain are not well understood. Here, we employed single-nucleus RNAseq, spatial transcriptomics, and T cell receptor (TCR) sequencing to analyze T cell and glial cell states in post-mortem PD brain tissue. CD8 + T cells were enriched in the PD SN and characterized by clonal expansion and TCR sequences with homology to those reactive to α-synuclein. Furthermore, PD T cells were spatially correlated with CD44+ astrocytes, which increased in the PD SN. Silencing CD44 in cultured astrocytes attenuated neuroinflammatory signatures, suggesting a potential therapeutic target. These findings provide insight into the neurodegenerative niche underlying T cell-mediated neuroinflammation in PD.